(1363) production planning models and linear programming - Hamza, Abdel-Kader (The Institute Of National Planning., 2018)
In the practical application of Operations research plays the leaner programming methods the main roll in solving many applied problems. This is based on their practical simple applications and also on their simple solution methods.